Metode Penelitian Hukum Progresif dalam Mengidentifikasi 'Pasal Karet' pada Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) dan Urgensinya bagi Demokrasi Digital - Sangkala, Robert; Komala, ⁠Ida; Wibowo, Satria Ari; Roif, Roif; Asari, Ali; Candra, Firman Adi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The digital era has revolutionized societal interactions, including expression and democratic participation. However, Indonesia's Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), revised twice (2016 and 2024), still contains ambiguous provisions known as